Opportunities for mobilizing recalcitrant phosphorus from agricultural soils: a review - Menezes-Blackburn, Daniel; Giles, Courtney; Darch, Tegan; George, Timothy S.; Blackwell, Martin; Stutter, Marc; Shand, Charles; Lumsdon, David; Cooper, Patricia; Wendler, Renate; Brown, Lawrie; Almeida, Danilo S.; et al. (Plant and soil, 2018)
Background Phosphorus (P) fertilizer is usually applied in excess of plant requirement and accumulates in soils due to its strong adsorption, rapid precipitation and immobilisation into unavailable forms including organic moieties. As soils are complex and diverse chemical, biochemical and biological systems, strategies to access recalcitrant soil P are often inefficient, case specific and inconsistently applicable in different soils. Finding a near-universal or at least widely applicable solution to the inefficiency in agricultural P use by plants is an important unsolved problem that has been under investigation for more than half a century. Scope In this paper we critically review the strategies proposed for the remobilization of recalcitrant soil phosphorus for crops and pastures worldwide. We have additionally performed a meta-analysis of available soil 31P–NMR data to establish the potential agronomic value of different stored P forms in agricultural soils. Conclusions Soil inorganic P stocks accounted on average for 1006 ± 115 kg ha−1 (57 ± 7%), while the monoester P pool accounted for 587 ± 32 kg ha−1 (33 ± 2%), indicating the huge potential for the future agronomic use of the soil legacy P. New impact driven research is needed in order to create solutions for the sustainable management of soil P stocks.